Competence pili in Streptococcus pneumoniae are highly dynamic structures that retract to promote DNA uptake. Issue 2 (16th April 2021) - Lam, Trinh; Ellison, Courtney K.; Eddington, David T.; Brun, Yves V.; Dalia, Ankur B.; Morrison, Donald A.
Abstract: The competence pili of transformable Gram‐positive species are phylogenetically related to the diverse and widespread class of extracellular filamentous organelles known as type IV pili. In Gram‐negative bacteria, type IV pili act through dynamic cycles of extension and retraction to carry out diverse activities including attachment, motility, protein secretion, and DNA uptake. It remains unclear whether competence pili in Gram‐positive species exhibit similar dynamic activity, and their mechanism of action for DNA uptake remains unclear. They are hypothesized to either (1) leave transient cavities in the cell wall that facilitate DNA passage, (2) form static adhesins to enrich DNA near the cell surface for subsequent uptake by membrane‐embedded transporters, or (3) play an active role in translocating bound DNA via dynamic activity. Here, we use a recently described pilus labeling approach to demonstrate that competence pili in Streptococcus pneumoniae are highly dynamic structures that rapidly extend and retract from the cell surface. By labeling the principal pilus monomer, ComGC, with bulky adducts, we further demonstrate that pilus retraction is essential for natural transformation. Together, our results suggest that Gram‐positive competence pili in other species may also be dynamic and retractile structures that play an active role in DNA uptake. Abstract : Competent pneumococci kill non‐competent cells on contact. Retractable DNA‐binding fibers in the type IV filament superfamily provide a key tool for retrieving DNA segments from cell wreckage for internalization and recombination.